Refining the Line of Distinction between Ethnic Conflict and Security Dilemma: Towards a Theory of Identity Driven Ethnic Conflict. Issue 3 (3rd July 2019) - Abushov, Kavus
ABSTRACT: The concept of security dilemma has been widely applied to ethnic conflicts in former Yugoslavia and the post-Soviet space. This paper argues that for both methodological clarity and policy formation, we should distinguish between ethnic conflicts caused by security dilemma and ones triggered by ethnic identity. It is argued that identity plays a different role in security dilemmas, but a major one in identity-based ethnic conflicts. Although ethnic identity may be at stake in the operation and dynamics of security dilemma, it is not the causal variable in the outbreak of ethnic conflict. Identity-based conflicts may reproduce many of the features of the security dilemma but have other causal factors. Distinguishing between the differing role of identity in security dilemma and identity based-ethnic conflicts may further our understanding of why certain conflicts have become so intractable, while others are relatively easier to resolve. For testing the hypothesis, empirical evidence is presented from two conflicts in the post-Soviet space with variations in the causal variable.